GENDER ASSIGNMENT IN COMPLETE ANDROGEN INSENSITIVITY SYNDROME. WHO SHOULD BE THE DECISION MAKER - Naveed Ahmed (Army Medical College Rawalpindi, 2020)
Androgen insensitivity syndrome (AIS) is a condition in which the target cells are unable to respond to androgenic hormones. This inability can be complete or partial. Although the individual is a genetic male due to the presence of Y chromosome but clinical presentation can vary ranging from a complete male to full female habitus. There are also individuals that lie in between these two extremes depending upon the severity of the condition. Gender assignment in such patients poses a great challenge for the care givers, parents and the patients. We report a very rare case of 10-year old phenotypic female who presented in outpatient department with bilateral inguinal hernia and during management she turned out to be a patient of complete androgen insensitivity syndrome (CAIS).